STUDY OF LIP PRINT PATTERN AMONGST THE STUDENTS OF NIMS MEDICAL COLLEGE (Journal of Forensic Medicine & Toxicology, 2018)
Lip prints are unique for each and every individual and is upcoming parameter for determination of individuality of a person. The study was done to determine the predominant lip print pattern amongst the students of NIMS Medical College and to see the correlation between gender and lip prints. The study has been conducted amongst the 400 students of NIMS Medical College, 200 males and 200 females in the age group of 18-24 years. Verbal consent is taken. The middle portion of lower lip was taken as study area and then lip prints were analysed by using Tsuchihashi’s classification. The order of frequency of lip print pattern among 400 students was I>III>I’>IV>II. The predominant pattern in males was Type III (25%) while in females the predominant pattern was Type I (32%). There is strong association between gender and lip prints which was calculated by using chi square and Pearson R.
Keywords: Cheiloscopy; Identification; Lip Prints; Medical Students